PENDAMPINGAN LEGALITAS USAHA MENUJU PENINGKATAN PEREKONOMIAN MASYARAKAT PURNA MIGRAN INDONESIA DI KECAMATAN BAWANG KABUPATEN BATANG - Khasanah, Dian Ratu Ayu Uswatun; Ronald Jolly Pongantung; Lita Tyesta Addy Listya Wardhani; Moh. Muzammil; Enny Dwi Lestariningsing; Eem kurniasih (Jurnal Bakti Masyarakat Indonesia, 2025)
ABSTRACT Tamarillo is a fruit that is rich in important nutrients. Apart from its delicious taste, tamarillo contains a variety of important nutrients, including vitamin C, antioxidants and fiber. This fruit has not been utilized optimally by the community because they do not know that it can be processed into a unique refreshing drink. Bawang District is an area in Batang Regency, Central Java. Several Bawang residents tried their luck abroad. Migrant workers who no longer continue their work contracts choose to return home and not go abroad again. Many of the former migrant workers feel confused when they return to their own country. based from this problems, one of the partner who have an entrepreneurship called NSR and the community service team are provide training and assistance to post-migrant workers who want to become entrepreneurs in their own country. The method used is 75% practice and 25% theory. Making Tamarillo juice is a solution for these former migrant workers to become entrepreneurs. The results of this community service were the skills of partners in making drinks who initially did not understand how to process them, market them, and the issuance of legality in the form of a HALAL certificate. The partners' ability to utilize Tamarillo into goods that have economic value means that post-migrant workers can earn their own income, although it is not as large as what they received when working abroad ABSTRACT Tamarillo is a fruit that is rich in important nutrients. Apart from its delicious taste, tamarillo contains a variety of important nutrients, including vitamin C, antioxidants and fiber. This fruit has not been utilized optimally by the community because they do not know that it can be processed into a unique refreshing drink. Bawang District is an area in Batang Regency, Central Java. Several Bawang residents tried their luck abroad. Migrant workers who no longer continue their work contracts choose to return home and not go abroad again. Many of the former migrant workers feel confused when they return to their own country. based from this problems, one of the partner who have an entrepreneurship called NSR and the community service team are provide training and assistance to post-migrant workers who want to become entrepreneurs in their own country. The method used is 75% practice and 25% theory. Making Tamarillo juice is a solution for these former migrant workers to become entrepreneurs. The results of this community service were the skills of partners in making drinks who initially did not understand how to process them, market them, and the issuance of legality in the form of a HALAL certificate. The partners' ability to utilize Tamarillo into goods that have economic value means that post-migrant workers can earn their own income, although it is not as large as what they received when working abroad. Keywords: community empowerment; people's economy; former migrants; Tamarillo; enterpreneur ABSTRAK Terong belanda adalah buah yang kaya akan nutrisi penting. Selain rasanya yang nikmat, terong belanda mengandung beragam nutrisi penting, termasuk vitamin C, antioksidan, dan serat. Buah ini belum dimanfaatkan secara maksimal oleh Masyarakat karena tidak mengetahui kalua bisa diolah menjadi minuma khas yang menyegarkan. Kecamatan Bawang merupakan wilayah yang berada di kabupaten Batang, Jawa Tengah. Beberapa penduduk Bawang mengadu nasibnya keluar negeri. Buruh migran yang sudah tidak meneruskan kontrak kerja lagi memilih untuk pulang kampung dan tidak berangkat lagi ke luar negeri. Banyak dari tenaga kerja purna migran itu yang merasa kebingungan ketika sudah pulang ke negerinya sendiri. Dari permasalahan mereka inilah mitra yang mempunyai wirausaha NSR tim PkM membuat pelatihan sekaligus pendampingan kepada pekerja purna migran yang ingin berwirausaha di negeri sendiri. Metode yang digunakan adalah 75% praktik dan 25% teori. Pembuatan minuman sari terong Belanda merupakan solusi untuk para pekerja purna migran ini dalam berwirausaha. Hasil PkM dosen ini adalah keterampilan mitra membuat minuman yang awalnya tidak paham mengolahnya, memasarkan, dan keluarnya legalitas berupa sertifikat HALAL. Kemampuan mitra untuk memanfaatkan terong Belanda menjadi barang yang mempunyai nilai ekonomi menjadikan pekerja purna migran bisa mendapatkan penghasilan sendiri walaupun tidak sebensar yang diterima saat bekerja di luar negeri.